On the influence of beryllium impurities on the transport properties of multicomponent arc plasma - Porytskyy, P.V. (Вопросы атомной науки и техники, 2014)
The influence of beryllium impurities on the transport properties of multicomponent arc plasma is considered in the ambient atmosphere of argon and carbon dioxide. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of metal causes the essential changes in the values of transport coefficients in comparison with the case of pure gaseous mixtures. It is revealed that the influence of the Ramsauer effect on transport properties can be neutralized by additions of metal into ambient argon. Рассмотрено влияние примесей бериллия на транспортные свойства многокомпонентной дуговой плазмы в атмосфере смесей аргона и диоксида углерода. Проведенные расчеты основывались на методе моментов Грэда. Показано, что незначительное количество примесей металла может существенно изменить величины транспортных коэффициентов в сравнении со случаем чистого аргона. Показана возможность нейтрализации влияния эффекта Рамзауэра на свойства плазмы путем добавки металлических примесей. Розглянуто вплив домішок берилію на транспортні властивості багатокомпонентної плазми в атмосфері сумішей аргону та диоксиду вуглецю. Проведені розрахунки ґрунтувалися на методі моментів Ґреда. Показано, що невелика кількість металевих домішок може суттєво змінити величини транспортних коефіцієнтів порівняно із випадком чистого аргону. Висвітлено можливість нейтралізації впливу ефекту Рамзауера на властивості плазми шляхом додавання металевих домішок.